2016
DOI: 10.1007/s00018-016-2409-5
|View full text |Cite
|
Sign up to set email alerts
|

A researcher’s guide to the galaxy of IRESs

Abstract: The idea of internal initiation is frequently exploited to explain the peculiar translation properties or unusual features of some eukaryotic mRNAs. In this review, we summarize the methods and arguments most commonly used to address cases of translation governed by internal ribosome entry sites (IRESs). Frequent mistakes are revealed. We explain why "cap-independent" does not readily mean "IRES-dependent" and why the presence of a long and highly structured 5' untranslated region (5'UTR) or translation under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 256 publications
3
70
0
Order By: Relevance
“…Based on further site-directed mutagenesis, the authors concluded that these G4s were part of IRESes (Internal Ribosome Entry Site), structures that initiate protein synthesis by a non-canonical 5'-cap-independent manner. While the presence of bona fide IRESes in viral genomes is well characterized, whether cellular IRESes exist is a matter of debate 146 . Under oxidative stress, the 5'-UTR of NRF2 mRNA (encoding the transcription factor NRF2, which regulates expression of antioxidant and detoxification genes) stimulates its translation in a G4-dependent manner 147 .…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%
“…Based on further site-directed mutagenesis, the authors concluded that these G4s were part of IRESes (Internal Ribosome Entry Site), structures that initiate protein synthesis by a non-canonical 5'-cap-independent manner. While the presence of bona fide IRESes in viral genomes is well characterized, whether cellular IRESes exist is a matter of debate 146 . Under oxidative stress, the 5'-UTR of NRF2 mRNA (encoding the transcription factor NRF2, which regulates expression of antioxidant and detoxification genes) stimulates its translation in a G4-dependent manner 147 .…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%
“…Normal protein synthesis was measured by the expression of full-length FLuc, and SCR was measured by the expression of NLuc when a PTC was inserted at position R154X (UGA). Importantly, by expressing each luciferase from a separate mRNA, we avoid many of the pitfalls that can confound interpretation of bicistronic reporters for studying stop codon readthrough (Loughran, Howard, Firth, & Atkins, 2017;Terenin, Smirnova, Andreev, Dmitriev, & Shatsky, 2017).…”
Section: Aminoglycosides Promote Ptc Readthrough While Simultaneouslymentioning
confidence: 99%
“…Our findings are reminiscent of the manner in which viruses use highly structured IRESs to directly recruit eIFs, the 40S subunit, and/or the 43S PIC to drive the cap-independent translation of viral mRNA (5,42,43). Although the mechanisms through which viral mRNAs use IRESs to drive cap-independent initiation have been extensively characterized using genetic, biochemical, and structural approaches (16,44,45), the mechanisms through which eukaryotic cellular mRNAs drive cap-independent initiation remain largely unknown.…”
Section: Discussionmentioning
confidence: 86%